(3QSGdI JbdjO GdebJfis ((3MeRg Hf Ydi Hf CMeO s)
(3ChdgG (B:s
(3JbdjOkG Vef EYde habc Gdehdi hefMc SHjd GdgOi hCYGPc ef GdZj hGdghi s
(3BNQgG (B:s
(3hfYe GdfUjQ GdeYjf SHMGfI hMOg dG TQjc dg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3QSGdg ef QSGFd GdOQhRs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3GdJhMjO hGdedd hGdfMds